2022
DOI: 10.1002/mrm.29494
|View full text |Cite
|
Sign up to set email alerts
|

An improved asymmetric susceptibility tensor imaging model with frequency offset correction

Abstract: Purpose To improve susceptibility tensor imaging (STI) reconstruction using the asymmetric STI model with the correction of non‐bulk‐magnetic‐susceptibility (NBMS) effects. Method A frequency offset term was introduced into the asymmetric STI model to account for the bias between measured MRI frequency signals and conventional susceptibility tensor models because of NBMS contributions. Experiments were conducted to compare the proposed model with conventional STI, conventional STI with the proposed frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Our simulations reveal that a predominant source of anisotropy in the STI tensor arises instead from the mesoscopic frequency from WM microstructure with only scalar susceptibility, that is, microstructural anisotropy. In fact, the apparent anisotropy was the same order of magnitude as the mean susceptibility, and in line with experimental findings for STI 16,27,28 . We also compared our maps to known STI tractography studies, 16,27,28 and found results strikingly similar to previous studies, including their characteristic deviation from standard DTI tractography.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our simulations reveal that a predominant source of anisotropy in the STI tensor arises instead from the mesoscopic frequency from WM microstructure with only scalar susceptibility, that is, microstructural anisotropy. In fact, the apparent anisotropy was the same order of magnitude as the mean susceptibility, and in line with experimental findings for STI 16,27,28 . We also compared our maps to known STI tractography studies, 16,27,28 and found results strikingly similar to previous studies, including their characteristic deviation from standard DTI tractography.…”
Section: Discussionsupporting
confidence: 88%
“…STI represents a natural extension of QSM to include macroscopic tensor anisotropy while still neglecting mesoscopic frequency shifts. Numerous studies have applied the STI model as a demonstration of WM susceptibility anisotropy 16,27,28 . However, microstructurally related frequency shifts in WM produce a large bias in STI 20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations